Fetal frontal cortex transplanted to injured motor/sensory cortex of adult rats. II. VIP-, somatostatin-, and NPY-immunoreactive neurons - Sharp, FR (J Neurosci, 1987)
Fetal frontal cortex transplants that survived 2–9 months in cavities in adult rat motor/sensory cortex were processed for vasoactive intestinal polypeptide (VIP), somatostatin 14 (SS), and neuropeptide Y (NPY) immunocytochemistry, and NADPH-diaphorase (NADPH-d) histochemistry. All transplants had surviving VIP, SS, NPY, and NADPH-d neuronal perikarya and fibers with normal adult morphology. The number of peptidergic neurons within transplants, however, often appeared to be less than that in equivalent areas of host cortex. Most transplanted SS and VIP neuronal perikarya did not migrate to form the laminae characteristic of normal cortex. A few transplants had SS and VIP cells arranged in laminae in which the VIP processes were parallel to one another and perpendicular to one transplant surface, approximating normal host neocortex. VIP, NPY, and SS fibers crossed between host brains and transplants, suggesting that peptide host-transplant interactions are possible. All adult host cortical and most transplanted NPY neurons colocalized with NADPH-d. The failure of some transplanted NPY neurons to express NADPH-d suggests these transplanted cells may be functionally impaired, but that they can survive without the NADPH-d enzyme.